Effect of nickel oxide addition on YBCO superconductor properties prepared by solid state reaction - Hairil Azwan Hosney (2017)
In this project, the YBCO superconductor was added with nickel oxide. The sample was prepared by mixing the chemical powder. Then, the mixed powder grounded and calcine at 900°C. After pelleting with 1 ton of pressure, the sample sintered at 960°C. There are a few test to investigate the performance of the samples. The sample characterizations are analyzed by using three technique such as XRD,XRF and resistivity measurement. The techniques are X-ray diffraction analysis to determine the structure and phase formation of the sample while the multi-meter to measure the resistivity of the sample at room temperature and XRF for elemental analysis. The sample with highest composition that is 0.12 wt% has the highest resistivity. XRD analysis result shows that the sample structure are slightly changing with the addition element NiO with composition NiO 0.08, 0.10, and 0.12 wt%. All the sample have orthorhombic structure and have different lattice parameter. The XRD also shows the addition element has decrease the sample porosity. To measure the sample resistivity, multi-meter was used in room temperature. A type of circuit was built and a battery with a voltage of 1.3 was used. At composition 0.08 wt%, the resistivity measure was 5.7307 ×10-3 Ωm. At composition 0.10 wt%, the resistivity calculated was 9.5513×10-3 Ωm. At composition 0.12 wt%, the resistivity calculated was 17.1924 ×10-3 Ωm. XRF analysis shows that there are a very small impurities in the sample. From the tests result, the higher the composition of NiO, the higher the resistivity of the sample. This can be proven by the reading of the resistance by the multimeter test.